How different agricultural research models contribute to impacts: Evidence from 13 case studies in developing countries. (September 2018) - Faure, Guy; Barret, Danielle; Blundo-Canto, Genowefa; Dabat, Marie-Hélène; Devaux-Spatarakis, Agathe; Le Guerroué, Jean Louis; Marquié, Catherine; Mathé, Syndhia; Temple, Ludovic; Toillier, Aurélie; Triomphe, Bernard; Hainzelin, Etienne
Abstract: In a context of a severe funding crisis, donors and policymakers expect increased accountability from research organizations and convincing proof that public investments in research have significant and positive societal impacts. This article takes stock of the lessons learned from the use of a method (ImpresS) designed by CIRAD to analyze the impact of research undertaken in partnership with a range of different actors in a developing-country context. The method uses a case study approach, and relies on the evaluation of the impact pathway and on contribution analysis. Thirteen case studies were selected to represent the diversity of partnerships, research activities and types of innovation. The results confirm the diversity and complexity of the innovation processes encompassing the non-linearity of changes over extended periods, the diversity of impacts, the shifting roles of actors engaged in the innovation process, and the diversity of activities carried out by the research community to contribute to outcome and impact generation. Interactions between researchers and other actors throughout the innovation process appeared to play key roles along the impact pathway. Based on the 13 case studies, we identified four generic models through which research contributes to impact: participatory transfer of knowledge and technologies, co-design of innovation, support for the innovation process, and promotion of open innovation. Our results underline the need for research institutions to recognize and accept the diversity of functions fulfilled by researchers if they want to contribute in an effective manner to the generation of impacts. Another challenge is to learn how to take advantage of clusters of projects embedded in innovation pathways in order to sustain research activities over a long timeframe. Significance statement: Impact evaluation is increasingly being requested from the research community as a measure of accountability by both donors and civil society. Conducting it properly is challenging, especially in the context of developing countries. Quantitative studies are often biased toward expected and tangible impacts. Complementary qualitative approaches are focused on understanding causality and are more in line with the actors' participation in impact evaluation. CIRAD has developed a method and used it to assess 13 case studies involving research conducted in partnership in widely differing environments. Some main lessons learned include the long timeframe needed for impacts to be achieved, the diversity of impacts the research community needs to consider, and the multiple roles played by the research community in co-developing outcomes with diverse stakeholders. Results show that the research community can contribute to impacts by using several models of intervention. Highlights: Research impact evaluation is increasingly being requested as a measure of accountability by both donors and civil society. Research impacts are more diverse than expected but a long timeframe is needed to be achieved There is a need to acknowledge the multiple roles played by researchers in co-developing outcomes with diverse stakeholders. Research community can contribute to impacts by using four generic research models of intervention.